The Influence of Corporate Governance on Enterprise Risk Management Implementation: A Study on Non-Financial Public Listed Companies in Malaysia: ERM Implementation and Corporate Governance - Md Sum, Rabihah; Abdul Khalik, Zakiah (Journal of Technology Management and Business, 2020)
This study investigates the influence of corporate governance on ERM implementation. The study focuses on non-financial public listed companies (PLCs) in Malaysia. The sample of the study is 44 non-financial public listed companies of the high-risk sectors: Energy, Utilities, and Telecommunications and Media. The objective of this study is to ascertain the effect of the size of the board, board independence, audit committee independence, financial education of the audit committee, size of the risk committee, and the independent risk committee on ERM implementation. ERM implementation is measured by ERM Score. Data is collected from published annual reports for the year ended 2016 and 2017. The study uses regression analysis to investigate the relationship between ERM implementation and corporate governance. The results, the size of the board and type of industry has significant influence on ERM implementation.